Surveillance of Antimicrobial Resistance in Intensive Care Setting at St Luke’s Hospital, Malta - Scicluna, Elizabeth Anne; Hanberger, Hakan (International Journal of Infection Control, 2007)
Knowing the resistance profile for the most common organisms that cause infections in a specific intensive care setting can help in guiding the intensivists when giving empiric antibiotic treatment, since adequate and timely treatment is of utmost importance to save lives. The main Intensive Care Unit (ICU) in St Luke’s Hospital is a 13-bed case-mixed ward, with 97% annual occupancy rate. To improve surveillance and control antibiotic resistance, we participated in Care-ICU (Controlling Antibiotic REsistance in ICU), a program for infection control surveillance part of the IPSE (Improving Patient Safety in Europe) project. The most common organisms isolated were Pseudomonas aeruginosa, Acinetobacter baumannii and Staphylococcus aureus. However, in blood cultures Enterococcus faecalis was third in 2005 and second in 2006, preceded only by P. aeruginosa. In respiratory specimen there was a shift from P. aeruginosa, with 33% of isolates in 2005 and 24% in 2006, to A. baumannii from 22% to 34%. Frequency of antibiotic resistance varies between species and sources. In blood, oxacillin resistance in S. aureus reached 86%. In P. aeruginosa and A. baumannii resistance to carbapenem was 19% and 86% and for 3rd generation cephalosporins was 44% and 85% respectively. Meropenem is the most common antibiotic used in this ICU with 1997.5 defined daily doses (DDD) in 2006. Several 3 rd generation cephalosporins are used including ceftriaxone (629 DDD), ceftazidime (139.8 DDD) and cefotaxime (49.5 DDD). Resistance rates in our ICU are very high when compared to other centres participating in CARE-ICU, for example the median resistance rate for carbapenem in A. baumannii is 12%. Feedback on antimicrobial resistance may be a useful tool to tackle misuse of antibiotics and emergence of antibiotic resistance. There is an urgent need for increased compliance to hygiene rules and improved infection control and the most efficient infection control interventions have to be defined